Factors Affecting Access to Higher Positions of Supporting Staff Rajabhat Maha Sarakham University - Jumpasri, Prayong (Journal for Developing the Social and Community, 2018)
This research aimed to (1) study of the supporting staff on access to higher positions in Rajabhat Maha Sarakham University and (2) analyze factors effecting access to higher positions for Rajabhat Maha Sarakham University supporting personnel. The target group of this research was 200 Rajabhat Maha Sarakham University supporting personnel. Taro Yamane formula was used to determine the size of the target group. Random sampling was also used to select the target group. The tool used to collect the data for this research was 5-scale rating questionnaire which had 64 items. The statistics used in analyzing the collected data were frequency, percentage, mean, standard deviation, F-test (One Way ANOVA), and multiple linear regression analysis. The Research results findings were: 1. The results of the collected opinions about the given factors affecting access to higher positions of the supporting staff Rajabhat Maha Sarakham Universitywere (1) Attitude towards their professions was at the highest level ( X =4.65), (2) Relationship between them and their organization was at the highest level ( X =4.61), (3) Motivation to do their work was at the highest level ( X =4.57), (4) Self improvement was at the highest level ( X =4.35), (5) University’s policies was at the highest level ( X =4.32), (6) Promotions and supports from their heads was at the high level ( X =4.19), and (7) Pressure from the surroundings was at the moderate level ( X =3.29). 2. For the access to higher positions, 123 out of the 200 supporting personnel, 61.50 in percentage, were still gathering and preparing information to create work portfolios (For example, work manuals, work-related research papers, and analytical or synthetically works) to be qualified and evaluated for higher positions. 38, 19 in percentage, had already had work portfolios and work manuals (For example, work manuals, work-related research papers, and analytical or synthetically works) to be qualified and evaluated for higher positions. 30, 15 in percentage, were interested in higher positions but hadn’t begun any preparation for the evaluation. 5, 2.50 in percentage, were in the process of applying for the evaluation to access to high positions. The factors affecting access to higher positions of the supporting staff Rajabhat Maha Sarakham University with a significant level of 0.01 were power motivation and type of personnel. The factors could predict a variance of the access to higher positions at 13.90 in percentage (R2=0.139, F=14.900) This showed that the power motivation could be a propellant for the supporting personnel to create their opportunities in accessing to higher positions; and type of personnel, as well, could strengthen the port unities.